THE INFLUENCE OF ENGLISH TEACHERS’ SPEECH FUNCTIONS ON STUDENTS’ COGNITIVE, BEHAVIORAL, AND EMOTIONAL LEARNING ENGAGEMENT: A LINGUISTIC SEMIOTIC STUDY IN INDONESIAN EFL CLASSROOMS - Mayasari; Misla Geubrina; Zuindra; Fuan Indri Maysha Siregar; Intan Kurnia Sari (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
The role of English teachers' speech functions as socio-semiotic resources is undeniably crucial in shaping student learning engagement, yet its psychological impact remains under-explored in Indonesian English as a Foreign Language (EFL) classrooms. This study aimed to systematically investigate the types of speech functions utilized by EFL educators and critically analyze their direct socio-semiotic impact on students' behavioral, emotional, and cognitive engagement. Employing a qualitative descriptive design framed within Systemic Functional Linguistics (SFL), the research involved twenty eleventh-grade students and their teachers over a four-week naturalistic observation period. Data were rigorously collected through high-fidelity audiovisual recordings, multidimensional engagement observation protocols, and stimulated-recall interviews for methodological triangulation. Preliminary baseline data indicated that 80% of the students exhibited merely low to moderate engagement, relying heavily on superficial behavioral compliance. The subsequent linguistic discourse analysis empirically revealed that the teachers' dominant use of unmitigated commands and declarative statements created a highly restrictive semiotic environment that actively stifled spontaneous participation. Conversely, the strategic deployment of authentic, open-ended questions and supportive pedagogical offers functioned as inviting semiotic signs that significantly elevated students' emotional security and cognitive effort. The study concludes that a teacher's linguistic choices are not neutral instructional mechanisms, but rather powerful semiotic instruments that fundamentally construct or deconstruct the psychological reality of the learning space..